2013
DOI: 10.1136/annrheumdis-2013-203223.1
|View full text |Cite
|
Sign up to set email alerts
|

A9.1 αvβ3 Integrin Inhibition with Cilengitide Both Prevents and Treats Collagen Induced Arthritis

Abstract: Background Rheumatoid arthritis (RA) is characterised by synovial inflammation and osteoclast (OC) mediated bone erosions. AlphaVbeta3 (αvβ3) integrin is highly expressed in OCs. Avβ3 blocking antibodies reduce bone resorption and mice lacking β3 are osteopetrotic. Objectives Efficacy testing of the αvβ3 inhibitor cilengitide, a synthetic Arginine-Glycine-Asparagine amino acid peptide (RGD peptide), on osteoclastogenesis and the collagen induced arthritis (CIA) model for human RA. Materials and MethodsIn vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…LXZ2 was identified as a new αvβ3 antagonist. It has IC50 of 0.09 μM (this value was converted to match with the IC50s in Table 3), which is comparable to LXW64 (0.07 µM) [8] and the first antagonistcilengitide-with IC50 of 0.25 µM [20]. In comparison with other RGD antagonists, LXZ2 as a LXW analog, not only shows a high binding affinity, but also likely exhibits the binding specificity against αvβ3 as previous studies showed that LXW peptides contain the auxiliary binding motifs including D-Asp at position 6 and the hydrophobicity of amino acid at X7 position [7,8].…”
Section: Discussionmentioning
confidence: 95%
“…LXZ2 was identified as a new αvβ3 antagonist. It has IC50 of 0.09 μM (this value was converted to match with the IC50s in Table 3), which is comparable to LXW64 (0.07 µM) [8] and the first antagonistcilengitide-with IC50 of 0.25 µM [20]. In comparison with other RGD antagonists, LXZ2 as a LXW analog, not only shows a high binding affinity, but also likely exhibits the binding specificity against αvβ3 as previous studies showed that LXW peptides contain the auxiliary binding motifs including D-Asp at position 6 and the hydrophobicity of amino acid at X7 position [7,8].…”
Section: Discussionmentioning
confidence: 95%